The Poetics of Sounds in the Poem “Maqam al-Buka for the Absence of the Dancer: or South of the Labyrinth” by the poet Mohamed Amine Saïdi - benhalis, houda (El Omda in Linguistics and Discourse Analysis, 2024)
The sounds in the poetic text constitute an effective stimulus to attract the recipient. The subject of the article concerns on the poetics of the vocal elements, through the poem "Maqam Boka Lighiab Al-ragisa: Ou djanoub el mataha" by the contemporary Algerian poet "Mouhamed El Amine Saidi", How did he take advantage of the richnesss of the alphabet in the systems of his poem to address the recipient in an impressive and aesthetically pleasing way? To answer, we take advantage of the methods of expressive stylistic mechanisms, and statistics with the help of the descriptive and analytical mechanism, reformulation, to combine poetic of sounds with connotations in the text